Students' understanding through the use of ICT-based accounting multimedia (MAKSI) in vocational high schools - Vivi Pratiwi; Siswandari Siswandari; Djoko Santosa Th (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This study aims to describe the use of MAKSI: Information and Communication Technology (ICT) based accounting multimedia in improving students' understanding on bank reconciliation material in Vocational High Schools (SMK). This research is a quantitative-descriptive research with case study method involving 40 students. Data collection techniques used are tests using essay tests, observations, and interviews. The result showed that the average understanding before using MAKSI is 52.18 with the less category, while after using MAKSI the average increases to 76.23 with good category. Before using MAKSI, 65% of students have less understanding, 27.5% have sufficient understanding, while 10% have good understanding. After using MAKSI, the percentage of the the students who have good understanding increases to 40%. In addition, there are 40% of students who have very good understanding. Those who have less understanding are only 7.5% while 12.5% of them have sufficient understanding. Thus, the use of MAKSI in learning in SMK can improve students' understanding.